Screening of Renal Function among a Group of Physicians Working in a Hospital Who are Often Self Neglected (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Prevalence of Chronic Kidney Disease (CKD) has been increasing rapidly worldwide and early screening to detect kidney disease, particularly at its early stages is pivotal to stop its further deterioration. Population-based study on detection at early-stage of kidney disease and it’s prevalence are scanty in our country, especially among the medical professional personnel. Hence taking advantage of the observance of World Kidney Day’ 2020, we conducted a screening pro-gram for kidney disease organized at the Chattagram Maa-O-Shishu Hospital (CMOSH) premises among a group of physicians of the hospital.Materials and methods: This was a cross-sectional observational study among 67 physicians of different ranks (Medical Officer to Professor) working at CMOSH in different discipline. Age, body weight, height, Body Mass Index (BMI), blood pressure were documented, and urinary protein and serum creatinine were measured at a single sitting. Kidney function was estimated by calculating the Glomerular Filtration Rate (GFR) using the Modification of Diet in Renal Disease (MDRD) formula. Kidney function was classified according to estimated GFR (eGFR) and Kidney Disease Outcomes Quality Initiative (K/DOQI) guidelines.Results: A total of 67 working physicians of the hospital were studied. Majority subjects (30) were in the age group of 20-29 years. Among all 11.9% participants had proteinuria (Trace to 1 plus). The distribution of eGFR was symmetrical, with the majority (70.10%) of subjects in the 60–89 ml/min category, 11.90% had 30-59 ml/min category and only 17.90% of the study population had eGFR > 90 ml/min. An inverse relation between eGFR and age, and a direct relation between eGFR and BMI were observed.Conclusion: Proteinuria low eGFR levels might be related with future decline in renal function among the studied subjects and so regular health check-up is important to abate the potential epidemic of kidney disease among the health professionals.Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 14-18